Sovereign ratings: Determinants and policy implications for India - Sanjay Sehgal; Shruti Mathur; Mamta Arora; Latika Gupta (IIMB Management Review, 2018)
This paper studies sovereign rating models of Moody's, Standard & Poor's (S&P) and Fitch to identify important determinants of sovereign ratings. Ordered logit and probit are employed to check for robustness of empirical results. We found that Moody's model is most reliable (it has the highest rate of correct predictions for sample countries). Further, the sovereign ratings are robust to the choice of estimation procedures. Economic strength, inflation and governance indicators are found to be important determinants of sovereign ratings followed by fiscal strength, domestic political risk and size of banking system. The paper provides key policy suggestions for India to improve its ratings. Keywords: Sovereign ratings, Credit rating agencies, Factor analysis, Ordered logit and probit, Economic factors, Governance indicators